1997
DOI: 10.1046/j.1365-2435.1997.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in leaf longevity of Pistacia lentiscus and its relationship to sex and drought stress inferred from leaf δ13C

Abstract: Summary1. Leaf formation, loss, retention, longevity and biomass on male branches of the evergreen mediterranean shrub Pistacia lentiscus, L. correlated strongly with wateruse efficiency inferred from leaf δ 13 C across a gradient of precipitation on the island of Mallorca, Spain. 2. The correlations suggest that the leaf phenology is under control of droughtinduced constraints on the carbon balance. 3. In fruiting female branches, the correlations between the inferred water-use efficiency and number of formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
2
25
1
1
Order By: Relevance
“…The d 13 C ‰ values of honey protein increase with increasing number of sunshine days/sunshine duration and thus with increasing mean temperature (Jonasson, Medrano, & Flexas, 1997) and decreasing average humidity, as it could be expected in the Mediterranean sampling regions like Carpentras, Chalkidiki, Sicily or Tuscany. The d 13 C ‰ values of honey protein from regions with lower mean temperatures or higher air humidity like Orkney (Scotland), Mühlviertel (Austria), Gäuboden (Germany) or Jylland (Denmark) accordingly exhibit lower d 13 C ‰ values than the Mediterranean honeys.…”
Section: Carbon Isotopessupporting
confidence: 60%
“…The d 13 C ‰ values of honey protein increase with increasing number of sunshine days/sunshine duration and thus with increasing mean temperature (Jonasson, Medrano, & Flexas, 1997) and decreasing average humidity, as it could be expected in the Mediterranean sampling regions like Carpentras, Chalkidiki, Sicily or Tuscany. The d 13 C ‰ values of honey protein from regions with lower mean temperatures or higher air humidity like Orkney (Scotland), Mühlviertel (Austria), Gäuboden (Germany) or Jylland (Denmark) accordingly exhibit lower d 13 C ‰ values than the Mediterranean honeys.…”
Section: Carbon Isotopessupporting
confidence: 60%
“…The nitrogen content of thylakoid membranes may decrease markedly during severe drought stress (Lösch 2001). On the other hand, drought stressed leaves contain less starch due to reduced rates of assimilation, thus increased nitrogen contents may also be caused by reduced dilution by carbon rather than by increased accumulation of nitrogen (Epron and Dreyer 1996;Jonasson et al 1997). The increase of SLA measured in all drought-treated plants (Table 2) and the unchanged concentrations of nitrogen when calculated on a leaf area basis (data not shown) support the latter hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis has been validated by investigations on different tree species (Reich et al 1991;Schulte 1992). Jonasson et al (1997) showed for Pistacia that the phenology of leaves is under the control of drought-induced constraints of the carbon balance.…”
Section: Resultsmentioning
confidence: 99%
“…Female plants, therefore, would not have had time enough to harden their tissues. Several studies have addressed ecophysiological differences between sexes of P. lentiscus with regard to their habitat preferences (Jonasson et al, 1997;Verdu´and Garcia-Fayos, 1998;Correia and Dı´az Barradas, 2000). However, to our knowledge, no phenological approaches have assessed such differences.…”
Section: Introductionmentioning
confidence: 99%